ORGANIZATION OF FIELD TRAINING FOR GEOGRAPHY STUDENTS IN THE FERGANA VALLEY - Odiljon Tobirov; Xidoyatkhon Abdinazarova; Azamjon Jobborov; Azamat Khoshimov (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Field training is a fundamental component of geography education, enabling students to integrate theoretical knowledge with real-world observation and analysis. This article examines the organization, significance, and methodological foundations of field training for geography students in the Fergana Valley, a region characterized by diverse natural landscapes, complex socio-economic conditions, and environmental challenges. The study highlights the educational value of hands-on fieldwork in developing students’ practical skills in geographical data collection, environmental assessment, and spatial analysis. Particular attention is given to logistical planning, site selection, safety considerations, and the use of modern technologies such as Geographic Information Systems (GIS) and remote sensing during field activities. The results demonstrate that well-organized field training enhances students’ critical thinking, professional competencies, and understanding of local environmental and cultural contexts. The article concludes that the Fergana Valley provides an effective and versatile field laboratory for geography education and offers recommendations for improving future field training programs through interdisciplinary approaches and technological integration.